2015
DOI: 10.1002/sia.5760
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial reactions of duplex stainless steels with molten aluminum

Abstract: The morphology and constitution of the intermetallic layers formed on the surface of duplex stainless steels (DSSs) immersed in molten aluminum at 750 °C for 30 min have been studied in detail by scanning electron microscopy and electron probe micro‐analyzer. Compared with H13 steel, the DSSs exhibited a better corrosion resistance. The weight loss rates, as expressed in terms of weight loss per square centimeter of the specimen per minute, of DSSs are smaller than that of H13. The thickness of the intermetall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The reason may be ascribed to the following aspects: On one hand, the 3D net-like structure of borides can protect the Fe-Al IMCs from spalling. On the other hand, the IMC layers can serve as barriers to weaken the inter-diffusion rate of molten aluminum and matrix, which leads to the improvement of the corrosion resistance [34,38]. However, when the immersion time is longer than 4 h, the intermetallic thickness of H13 steel is decreased.…”
Section: Resultsmentioning
confidence: 99%
“…The reason may be ascribed to the following aspects: On one hand, the 3D net-like structure of borides can protect the Fe-Al IMCs from spalling. On the other hand, the IMC layers can serve as barriers to weaken the inter-diffusion rate of molten aluminum and matrix, which leads to the improvement of the corrosion resistance [34,38]. However, when the immersion time is longer than 4 h, the intermetallic thickness of H13 steel is decreased.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the dissolution process is known to be controlled by diffusion and preferential leaching of Ni, and in a second step of Cr, migrating towards the surface of the material and segregating in sites where a minute amount of oxygen is present. The dissolution of the iron matrix occurs only after Ni and Cr are sufficiently depleted [53,54]. It can also be appreciated that the sample annealed for 360 s/mm possesses one of the poorest content of Ni and Cr within the ferritic phase (Table 5), testifying the key role of these alloying elements in these liquid metal erosion/corrosion phenomena.…”
Section: Discussionmentioning
confidence: 96%
“…Cr is another important alloying element to improve the corrosion resistance of mild steels. Zhang et al [67] suggested that Cr-rich duplex stainless steel enjoys a better corrosion resistance to liquid aluminum than H13, whose interface between the reaction layer and matrix is much flatter. Its reaction layer is found to consist of outer porous (Fe, Cr)Al3 and inner continuous (Fe, Cr)2Al5.…”
Section: Alloyingmentioning
confidence: 99%